The influence of behavioral methods on the formation of academic discipline (MMIT Proceedings, 2025)
The article examines the influence of behaviorist methods on the formation of academic discipline. It analyzes the basic principles of behaviorism, the use of reinforcement and punishment systems in educational practice. Special attention is given to the effectiveness and limitations of these methods in managing student behavior. The integration of behaviorist approaches with other learning theories to enhance motivation and establish sustainable academic discipline is also discussed